"No One's Coming to Save Us": Centering Lived Experiences in Rural Food Insecurity Organizing. Issue 8 (3rd July 2021) - Ivancic, Sonia R.
ABSTRACT: This essay draws on fieldwork with a nonprofit organization in Southeast Ohio in order to gain insight into the unique challenges of rural food insecurity. A series of narrative vignettes illustrate how these challenges are maintained through dominant narratives about what food insecurity, charity, poverty, and ruralness "look like." These moments disrupt the binary categories of who gives and who receives aid, and they illuminate how stereotypes and uniformed "solutions" can hinder efforts to create rural food security. Last, this research shows how the people of Southeast Ohio are harnessing regional assets to create collaborative, creative solutions to food access.